FAKTOR-FAKTOR YANG MEMPENGARUHI MUNCULNYA STRES KERJA PERAWAT DI RUANG RAWAT INAP CENDRAWASIH RSUD ARIFIN AHMAD PROVINSI RIAU PEKANBARU - Rahmadyrza, Muhammad Iqbal; Ningsih, Dewita Suryati; Pramadewi, Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research held in impatient room RSUD Arifin Ahmad Riau Province Pekanbaru in order to analyze the influence of workload, work safety & health and non-psychal work environment to nurses’ work-related stress. Population are all nurses, consist of 69 people, that considering the number limitation so sampling method used is census. Data analyzed by using descriptive and multiple linier regression analysis. Result of this study shows that workload, work safety & health and non-psychal work environment simultenously influence the nurses’ work-related stress. Partially, the more heavier workload becomes, the higher work-related stress will emerge. Meanwhile, the better work safety & health programs implemented and more conducieve the non-psychal work environment becomes, the both factors may reduce the stress level in the work place. Workload becomes the strongest factor that influence stress level in work place compared to the effect of work safety & health and non-psychal work environment. It is recommended to conduct a proportional workload analysis, effectizing the work safety & health program and harmonizing all aspects in non psychal work environment so that the stress level may be optimally organized.Keywords: Workload, Work Safety & Health, Non Psychal Work Environment and Work-related Stress